2015
DOI: 10.1002/eqe.2673
|View full text |Cite
|
Sign up to set email alerts
|

Running safety assessment of trains moving over bridges subjected to moderate earthquakes

Abstract: SUMMARYA study about the running safety of trains moving over bridges subjected to earthquakes is presented. The study focuses on moderate earthquakes with relatively small return periods and high probability of occurrence. The analyses are performed using a nonlinear train-bridge interaction method proposed by the authors, being the running safety evaluated with safety criteria existent in the literature. The influence on the train running safety of the seismic intensity levels, train running speed, and track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Zhang et al , examined the seismic non‐stationary random response of 3D train–bridge systems. Recently, Montenegro et al , studied the dynamic stability of trains moving over bridges subjected to seismic excitations. Further, Montenegro et al , proposed a wheel–rail contact model for analyzing the nonlinear lateral train–structure interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al , examined the seismic non‐stationary random response of 3D train–bridge systems. Recently, Montenegro et al , studied the dynamic stability of trains moving over bridges subjected to seismic excitations. Further, Montenegro et al , proposed a wheel–rail contact model for analyzing the nonlinear lateral train–structure interaction.…”
Section: Introductionmentioning
confidence: 99%
“…But these two exact models are only suitable for one wheel/rail rolling contact simulation due to the very expensive computation cost at the current stage. Thus, some approximate models, such as the FASTSIM, USETAB, Vermeulen-Johnson, Shen-Hedrick-Elkins, Polach methods, are commonly used for fast calculation applications of the train-track-bridge dynamic simulations [23,32,78,79,[83][84][85].…”
Section: Wheel-rail Dynamic Interaction Modelmentioning
confidence: 99%
“…Xu and Zhai (2017) developed a stochastic analysis model of vehicletrack systems subjected to earthquake and track random irregularities and found that lateral seismic waves have a great influence on lateral vibrations of trains and tracks but slight impacts on vertical vibrations. Some researchers also studied the derailment responses of railway vehicles on bridges (Montenegro et al, 2016;Xia et al, 2006;Yang and Wu, 2002;Zeng et al, 2015). The above research studies on train-track responses are mainly proceeded in simulation, whereas the subgrade is not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%